Clinics - Pintos Fuentes, Raúl; Martínez Apezteguía, José Luis (Cirugía del Uruguay, 1974)
They are rare tumors. Sabiston and Scott (9) found a primitive mediastinal tumor every 3,400 admissions at J'ühn Hopkins Hospital. Wychulis et al. (13), in a 40-year review by the Mayo Clinic, they found 1,064 mediastinal tumors.